BATIK GAMES: OPTIMALISASI SALURAN KOMUNIKASI BISNIS UMKM MELALUI PERANCANGAN DAN PEMBUATAN MATERI INTERAKTIF H5P - Putri Sekarsari; Wahyuni Ningsih; Noverita Wahyuningsih; Sugeng Hariyanto; Eko Boedhi Santoso; nugrahaningtyas fatma anyassari (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2026)
In an increasingly competitive business environment, an SME batik, with its inherent product strengths, needs to optimize its business communication channels by relying not only on static materials but also on interactive ones. This community service activity was carried out to equip the batik MSME website with interactive materials titled 'batik games'. The community service implementation method included designing and creating the interactive materials, which consisted of four stages: design, production, internal evaluation, and field testing; measuring the level of partner empowerment; and product handover. The H5P plug-in was chosen to accommodate product creation. Ten interactive games in two languages ​​(Indonesian and English) were created. Field testing results show that respondents agreed that the H5P interactive materials on the 'batik games' page were fun and useful. The interactive materials were fun because they were exciting, interactive, and informative. The materials were useful because they added insight into batik patterns, meanings, and methods of batik making as well as the culture related to the batik patterns through an interesting way for Gen Z. The results obtained from the analysis of increasing the level of partner empowerment are an increase in partner competitiveness in terms of adding a variety of business communication channels, increasing differentiation of business communication strategies, and adding English as the language ​​for business communication channel materials. Keywords: SME batik, business communication, interactivity, English